2020
DOI: 10.1002/smll.202001450
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Ferritin Nanoparticles for the Bioluminescence Tracking of Nanodrug Delivery in Cancer

Abstract: The identification of a highly sensitive method to check the delivery of administered nanodrugs into the tumor cells is a crucial step of preclinical studies aimed to develop new nanoformulated cures, since it allows the real therapeutic potential of these devices to be forecast. In the present work, the ability of an H‐ferritin (HFn) nanocage, already investigated as a powerful tool for cancer therapy thanks to its ability to actively interact with the transferrin receptor 1, to act as an efficient probe for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…However, in addition to the wide binding specificity of a variety of integrins, it has been reported that repeated administration of integrin αvβ3-targeting RGD peptides would most likely trigger immunogenicity [ 44 ]. Furthermore, the distribution and number of the targeting ligands, Arg-Gly-Asp (RGD), modified on the ferritin nanocarrier surface have the significant impact on efficacy of active tumor targeting [ 45 ]. The surface ligand pattern should be optimized to fit the receptor clustering feature to achieve the best tumor targeting.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to the wide binding specificity of a variety of integrins, it has been reported that repeated administration of integrin αvβ3-targeting RGD peptides would most likely trigger immunogenicity [ 44 ]. Furthermore, the distribution and number of the targeting ligands, Arg-Gly-Asp (RGD), modified on the ferritin nanocarrier surface have the significant impact on efficacy of active tumor targeting [ 45 ]. The surface ligand pattern should be optimized to fit the receptor clustering feature to achieve the best tumor targeting.…”
Section: Discussionmentioning
confidence: 99%
“…As the globally commercialized CSFV lapinized vaccine strain C failed in serological DIVA (differentiation between infected and vaccinated animals), the application of a novel ferritin nanoplatform with soluble E2 antigen provides a candidate for vaccine development for the eradication of the CSFV pandemic. Numerous self-assembling ferritin-associated studies showed that the exposed antigens or proteins were produced in native status and arranged in well-ordered manners, such as a bioluminescent tracer for liver cancer detection and receptor binding domain decoration for COVID-19 elimination [28,29]. Furthermore, the 24-subunit polymer was efficiently phagocytosed by body antigen recognition and presentation systems with a sensitive and potent neutralizing antibody response in vivo (see Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
“…The nanoparticles were bound and purified using an Ni-NTA affinity column [28]. The sample supernatant was loaded at a rate of 1.0 mL/min, and the column was washed with 5 column volumes (CV) of buffer A (0.1 M PBS, 300 mM NaCl, 5 mM imidazole) at 1 mL/min.…”
Section: Histidine (His) Tagged Affinity Purificationmentioning
confidence: 99%
“…Intracellular GSH can break the disulfide bond and release free luciferin. Luciferin is able to react with luciferase and perform bioluminescence imaging [173] modified iron oxide nanoparticles was rich in amine groups. Compact HSA coating could be realized just by adsorbing due to the natural multivalency and good solubility of protein-based nanoparticles.…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%